2020
DOI: 10.1155/2020/3262370
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calliandra and Sesbania on Daily Milk Production in Dairy Cows on Commercial Smallholder Farms in Kenya

Abstract: ere is a growing interest in protein supplementation of dairy-cow diets using leguminous shrubs. e study objective was to ascertain the association between diet supplementation with Calliandra calothyrsus and Sesbania sesban and milk production in dairy cattle on commercial smallholder farms. is trial involved 235 cows from 80 smallholder dairy farms in Kenya randomly allocated to 4 intervention groups: (1) receiving Calliandra and Sesbania and nutritional advice; (2) receiving reproductive medicines and advic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
(27 reference statements)
2
12
0
Order By: Relevance
“…The current results were also highly related to the findings by [28] that feeding dairy meal to a cow before calving period was associated with milk production increase by approximately 1.4 kg/day during the first 60 days of lactation. According to the findings by [29], the mean milk production for cows increased by 0.8% per cow per day with every kg increase in maize silage fed to cows.…”
Section: Feed Supplementation Effect On Milk Revenuementioning
confidence: 99%
“…The current results were also highly related to the findings by [28] that feeding dairy meal to a cow before calving period was associated with milk production increase by approximately 1.4 kg/day during the first 60 days of lactation. According to the findings by [29], the mean milk production for cows increased by 0.8% per cow per day with every kg increase in maize silage fed to cows.…”
Section: Feed Supplementation Effect On Milk Revenuementioning
confidence: 99%
“…The dry season in Eastern Africa is associated with low or no rainfall, and feed for smallholder dairy cattle advances in maturity and declines in quantity and quality, compromising feeding systems [11], [54,60,61]. These are the conditions under which the ability of the animal to derive nutrients from the diet are restricted, not only by the highly refractory nature of plant fibre to microbial attack, but also by the decline of protein and minerals to inadequate levels for both the fermentative microbes and the tissues of the animal [62].…”
Section: Feeding Frequency and Feed Intakementioning
confidence: 99%
“…Therefore, parallel to increased milk yields and lower feeding costs, which result in improved profit margins by implementing high quality feeds or optimized feeding strategies, there may be an enhanced sustainability not only in the economic scale, but also in the social scale from better incomes, and in the environmental scale from lower greenhouse gas (GHG) emissions. [60], sought to determine factors affecting milk production cost in SDFs using a multiple regression model. and reported that some factors such as the time spent in dairy cattle farm, farmers' dairy farming experience, farmers' educational level, farmers' feed procurement and conservation, livestock pests and diseases, farm-made roughage and maize silage production in the farm had significant effects on milk production costs.…”
Section: Feeding Strategies and Costmentioning
confidence: 99%
“…The leaves and pods/fruits of forage trees and shrubs are rich in nutrients and are valued by various ruminants (Ali et al., 2020; Weldemariam & Gebremichael, 2015) and therefore have the potential to partially or completely replace feed concentrate (Franzel et al., 2014). Several studies have shown that the inclusion of the leaves and pods/fruits of fodder trees and/or shrubs in the fibre‐based diet of ruminants improves feed intake, digestibility, growth, and productivity performance (Hlatini et al., 2016; Makau et al., 2020; Shenkute et al., 2012).…”
Section: Introductionmentioning
confidence: 99%